The Optimization of Gel Preparations Using the Active Compounds of Arabica Coffee Ground Nanoparticles - Salfauqi Nurman; Ruka Yulia; Irmayanti; Erliza Noor; Titi Candra Sunarti (MDPI AG, 2019)
Arabica coffee (Coffea arabica L.) ground nanoparticles contain phenolics compounds that have anti-inflammatory effects, so they can be used as sources of active compounds in anti-inflammatory gel preparations. This study aims to determine the optimum formulation of anti-inflammatory gel preparations using Arabica coffee ground nanoparticles as active compounds. Treatment optimization was performed using a Response Surface Methodology according to the Box-Behnken Design with a quadratic model in the Design Expert Version 10.0.3.0 software. In this study we used three factors (x): carbopol 940, triethanolamine (TEA), and nanoparticles, each of which consists of three levels, the response (y) observed including the acidity degree (pH), spreadability, viscosity and total phenolic content. ANOVA analysis results show that the quadratic model is very appropriate since it produces a high R2 value and a low PRESS value for all responses, as well as significant p-values (<0.0500) and an insignificant lack of Fit values (p-value> 5%). The optimum formulations for the gel preparations of the Arabica coffee ground nanoparticles obtained in this study are carbopol 940 (0.569%), TEA (0.468%), and nanoparticles (3.000%), which have values w/o an interval (0.994) and a desirable (0.981) response to acidity (5.212), spreadability (5.850 cm), viscosity (3734.244 cps) and total phenolic content (669.227 µgGAE/g).